2009
DOI: 10.4161/cbt.8.2.7114
|View full text |Cite
|
Sign up to set email alerts
|

Skp2 and salivary cancer

Abstract: Salivary malignancies are rare, heterogeneous, unpredictable in clinical behavior and seldom studied. Skp2 expression was examined in salivary malignancies (n = 75) for a prolonged period (20 years). In 40/75 (53%) cases Skp2 expression rate (staining level) was ≤4% while in the remainder (47%) it was >4%. Correlation between enhanced Skp2 and enhanced p53 staining levels was significant (p = 0.042), as were correlation rates between enhanced Skp2 and reduced p27 staining levels (p = 0.01) and enhanced Skp2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…The SKP2 gene is a newly discovered cancer gene that is overexpressed in many cancers such as in gastric, lung, colon, prostate, ovarian, and laryngeal cancers, and in glioma (Lu et al, 2002;Takanami, 2005;Ben-Izhak et al, 2009;Shi et al, 2011;Wei et al, 2013). SKP2 is a member of the F-box protein family, which is necessary for DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…The SKP2 gene is a newly discovered cancer gene that is overexpressed in many cancers such as in gastric, lung, colon, prostate, ovarian, and laryngeal cancers, and in glioma (Lu et al, 2002;Takanami, 2005;Ben-Izhak et al, 2009;Shi et al, 2011;Wei et al, 2013). SKP2 is a member of the F-box protein family, which is necessary for DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that, in small cell carcinomas, CK20-negative cases have a worse prognosis than the positive cases [51]. Bcl-2 (for adenoid cystic carcinoma) [37], E-cadherin (for adenoid cystic carcinoma) [26], p27 (for adenoid cystic carcinoma and mucoepidermoid carcinoma) [57, 73], MUC1 (for mucoepidermoid carcinoma) [28], glucose transporter type 1 (for salivary gland carcinoma) [46], heparanase [6], pRb2/p130 [61], vascular endothelial growth factor (for adenoid cystic carcinoma) [82], survivin [23, 72], RB1-inducible coiled-coil 1 [74], geminin [80], p63 (for adenoid cystic carcinoma) [60], Skp2 [7], EGFR [20, 21], c-kit [20], RUNX3 (for adenoid cystic carcinoma) [31], Cks1 [52], topoisomerase IIα [42], maspin [64], PI3K/AKT/mTOR [22, 75], and PTEN [21] were also reported to be significant IHC markers for evaluating the malignancy of the salivary gland carcinoma and for their prognostic estimation [65, 71]. …”
Section: Evaluation Of Malignancy and Prognostic Factorsmentioning
confidence: 99%
“…STAT1 [6], SKP2 [7], IFI16 [8], RHEB [9], FIF44 [10], SOD2 [11, 12], and GREM1 [11] are related to OSCC. Table 6 [13-56] summarizes the previous studies that have published the relations of selected genes with cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In salivary cancer, survival probability rates dropped when Skp2 was overexpressed [7]. Overexpression of Skp2 is associated with the reduction of p27 (KIP1) expression and may have a role in the progression of OSCC [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation